THE CONJUGALISATION OF REPRODUCTION IN SOUTH AFRICAN TEENAGE PREGNANCY LITERATURE - Macleod, Catriona (PINS-Psychology in Society, 2026)
The "conjugalisation of reproduction", in which childbearing is legitimated only within a marital alliance, underlies some of the pathologisation of the single, female-headed household in the pre-democracy South African teenage pregnancy literature. I utilise a post-structural feminist framework that draws on elements of Derrida’s and Foucault’s work to analyse the conjugalisation of reproduction in South African research. The conjugalisation of reproduction relies on (1) the insidious "unwed" signifier which interpenetrates the term ’teenage pregnancy’; allowing the scientific censure of non-marital adolescent re-production without the invocation of moralisation, and (2) the fixation of the husband-wife and parents-children axes of alliance as the main elements for the deployment of sexuality and reproduction in the form of the family. Pregnant teenagers are, in Derridean terms, undecidables: they are neither children (owing to their reproductive status) nor adults (owing to their age), but simultaneously both. Marriage is the authority that decides them, allowing them to join the ranks of adult reproductive subjects.